Main Sources of Reserves of Increase in Profit of the Organization - Igor Vladimirovich Lastovka (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article considers different approaches to the identification of the sources of income and the management of processes of formation of profit in industrial organizations, an important place is given to the issues of control over costs.